Does the Affordability of Housing Always Guarantee Access to an Ideal Home? - Cetinkaya, Almira Yilmaz; Yerliyurt, Bora (KARE PUBL, 2025)
This study argues that addressing the housing problem in Turkey and globally solely in financial terms is insufficient. While affordability is important, factors like housing condition, security, and the environment also impact quality of life. Households' needs and living standards are shaped by both financial resources and their social and physical surroundings. Therefore, to ensure the sustainability of housing rights, both the condition of the housing and the demands of the household must be considered. After 2019, the housing problem worsened globally due to the social and economic impacts of the pandemic. As purchasing power declined in Turkey and worldwide, housing prices for rent and sale soared, driven by high inflation. While housing research has largely focused on affordability, it often overlooks the condition of the homes people live in. This gap highlights the need for a more comprehensive approach to problem, one that considers both affordability and the quality and suitability of the housing itself. This study examines housing problems related to household behavior and housing conditions, even when house is affordable. By examining parameters such as socioeconomic-statues, integrated earthquake risk, neighborhood average-rent-prices; through all analysis for Istanbul we found that the B & uuml;y & uuml;k & ccedil;ekmece, H & uuml;rriyet Neighborhood had the lowest housing affordability but also the highest integrated earthquake risk; surveys conducted with homeowners and tenants. Research identified issues such as inadequate personal space, high transportation costs and living in earthquake-risk housing. As a result, we found that, apart from affordability, there is a problem of housing accessibility requested by the household.
Keywords: Affordability; household behaviour; housing accessibility; quality housing; NEED; Public Administration